The Investigation of Icon Concreteness with and without Text Describe for Retirees - Kleddao Satcharoen (My University, 2019)
The purpose of this study was to examine icon design for retirees, focusing on icon concreteness.The study was undertaken because although older adults are increasingly likely to use computers, the Internet, and portable computing devices like smartphones and tablets, they still face usability challenges including cognitive and skill barriers.Previous research has shown that concrete icons increase selection accuracy for inexperienced users.This research was an experiment (n = 30), in which users were asked to identify concrete and abstract icons.Chi-square analysis did not show a significant difference in selection accuracy of abstract and concrete icons in an unprompted trial ( 2 = 1.493, df = 5, p = .914)or a text-prompted trial ( 2 = .715,df = 3, p = .870).However, results were significantly better for the prompted trial.The implication is that abstract and concrete icons are equally difficult for senior adults to recognize.On the global scale, computer and Internet use is becoming more common, though it is not yet ubiquitous.As of December 2017, 51% of the world's population had Internet access, although this access is not evenly distributed between global regions *1+.A global average of 38% of adults have computers available in their households *2+.However, the biggest boost for computing power has been the emergence of mobile computing devices like tablets and smartphones, which are both cheaper and easier to use than fixed computers.As of 2015, there were an estimated 1.86 billion smartphone users worldwide, a figure which is expected to rise to 2.87 billion worldwide by 2020 *3+.However, this increasing computer and Internet access is not evenly spread.There is a long-standing digital divide, in which factors like age, education, socioeconomics, and location determine to some extent whether an individual will use computers and the Internet *4+.One element of the digital divide is ageolder users have long been known to use computers and the Internet at a lower rate than younger users *5+.There is some evidence that this difference is weakening, with now only the oldest seniors showing significant usage differences *5+.However, senior users still face significant user interface issues with computers, which have not been explored in enough detail to optimize computers for their use.This study's purpose was to examine one small aspect of the computer usage needs of seniorsthat of icon design, specifically icon concreteness.
Keywords: Concreteness; Icon; Handwritten Text Recognition Techniques